Problems of elderly women: need for interventions - V, PADMAVATHI; A, KALAIMATHI (Journal of Management and Science, 2012)
Elderly problem is a major problem across the world, as the elderly population is growing due to increase in health facilities. Among the elderly people, elderly women are most vulnerable group of the society suffering from socio-economic and health problems. The extents of problems of elderly women are more if they are widows. The paper analyzed the statistics of the elderly population and discussed the problems faced by elderly women in India. It is found that there is no particular social welfare scheme available for the betterment of health problems of the elderly women. Hence, the paper concluded with the remarks that there is need for health scheme for the elderlywomen.